“My Mother Told Me that Fat Girls Don’t Have Friends”: Mothers’ Messages about Gender to their Children - Heisler, Jennifer M. (Journal of the Motherhood Initiative for Research and Community Involvement, 2014)
Assuming intergenerational socialization occurs in the family, the current study explored how mothers influence future generations’ understanding of gender roles through the communication of “memorable messages” (Knapp, Stohl and Reardon). Ninety-five university students completed open-ended questionnaires recalling verbally communicated gendered messages from mothers. Results showed 99 percentof participants could recall a gendered message (N = 112); Recalled message themes included relationships (n = 55), equality (n = 35), and self-sufficiency (n = 20). Discussion of these findings focuses on the prevalence of traditional gender roles ideologies,the intergenerational nature of mother-child communication, and extensionsto the memorable message literature.